Ketoacidosis at first presentation of type 1 diabetes mellitus among children: a study from Kuwait - Shaltout, Azza Aly (Sci Rep, 2016)
We examined the frequency and severity of diabetic ketoacidosis (DKA) in 679 children and adolescents (0–14 years) at diagnosis of Type 1 Diabetes Mellitus (T1DM) in Kuwait. Between 1(st) January 2011 and 31(st) December 2013, all newly diagnosed children with diabetes were registered prospectively in a population-based electronic register. DKA was diagnosed using standard criteria based on the levels of venous pH and serum bicarbonate. At the time of diagnosis, mild/moderate DKA was present in 24.8% of the children, while severe DKA was present in 8.8%. Incidence of ketoacidosis was significantly higher in young children less than 2 (60.7% vs 32.4% p = <0.005) compared to children 2–14 years old, and a higher proportion presented with severe DKA (21.4% vs 8.3% p = <0.05). No association was seen with gender. Significant differences were found in the incidence of DKA between Kuwaiti and non-Kuwaiti children (31.1% vs 39.8%; p < 0.05). Family history of diabetes had a protective effect on the occurrence of DKA (OR = 0.44; 95% CI = 0.27–0.71). Incidence of DKA in children at presentation of T1DM remains high at 33.6%. Prevention campaigns are needed to increase public awareness among health care providers, parents and school teachers in Kuwait.